Analisa Layanan Sistem Informasi Online Shop Produk Kecantikan pada PT. Cantika Alami Indonesia - Muhammad Adam; Ahmad Taufik (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
This study aims to analyze the service quality of the online shop information system for beauty products at PT. Cantika Alami Indonesia. The research focuses on identifying the company’s needs, challenges in system development, and the benefits of better system implementation. Data collection methods include observation, interviews, questionnaires, and literature review. The findings reveal that the user aspect achieved a satisfaction score of 79.07%, indicating positive acceptance and experience. The functional aspect scored 75.54%, suggesting that the system functions well, though further improvements are needed. Meanwhile, the non-functional aspect received a score of 65.18%, highlighting the need for enhancements in performance and accessibility. Overall, the online shop system is rated well by users, but there is room for improvement, particularly in non-functional aspects. This study is expected to serve as a reference for companies and business practitioners in improving their e-commerce information systems to better meet consumer needs.